Ten-year outcome of vagus nerve stimulation-implanted patients with treatment-resistant depression: two Italian cases - Dell'Osso B (Dove Medical Press, 2018)
Bernardo Dell’Osso,1–3 Lucio Oldani,1 Benedetta Grancini,1 Alessandro Dario,4 A Carlo Altamura1 1Department of Psychiatry, University of Milan, Fondazione IRCCS Ca’ Granda, Ospedale Maggiore Policlinico, Milan, Italy; 2Department of Psychiatry and Behavioral Sciences, Bipolar Disorders Clinic, Stanford Medical School, Stanford University, Stanford, CA, USA; 3CRC “Aldo Ravelli” for Neurotechnology and Experimental Brain Therapeutics, University of Milan, Milan, Italy; 4Department of Neurosurgery, Macchi Foundation Hospital, Varese, Italy Abstract: Over the last 15 years, vagus nerve stimulation (VNS) has been used as an augmentative therapeutic intervention in patients with treatment-resistant depression (TRD), whether with a lifetime diagnosis of major depressive disorder or bipolar disorder. From being a potentially effective treatment in the acute phase of TRD, recently published treatment guidelines seemed to converge on the indication that VNS’s greatest benefit may be seen mostly beyond the short term. However, with the exception of a recent multicenter American report, very few studies have assessed the long-term efficacy of VNS in TRD patients. Herein, we present the cases of two Italian patients with TRD, with 10-year VNS follow-up evaluation. Both patients were found to benefit from augmentative VNS, and the latency of their stimulation response, tolerability, associated pharmacological treatment, number and duration of recurrences, and overall level of functioning are described and discussed. Further reports with larger samples are needed to support the long-term efficacy and tolerability of VNS in TRD patients, particularly beyond 5 years of follow-up. Keywords: vagus nerve stimulation, treatment-resistant depression, long-term follow-up, MDD, bipolar disorder